1999
DOI: 10.1111/j.1744-6198.1999.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and People With Poetentially Fatal Diagnoses

Abstract: When individuals must deal with potentially fatal diseases their lives change in many ways. This qualitative study was designed to investigate this critical life event. The authors interviewed a convenience sample (N = 15) of 10 women with cancer and 5 men with HIV/AIDS. Findings suggest that spirituality is an essential component to feelings of health and well-being. Many of the subjects viewed spirituality as a bridge between hopelessness and meaningfulness in life. Those who had found meaning in their disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 12 publications
2
45
1
3
Order By: Relevance
“…As professionals, it is important to pick up on clues from patients, as informal spiritual assessment can take place anytime-for example, discussions around the search for meaning and making sense or fear or what the future holds may indicate spiritual distress [1]. Patients can then be helped to address this distress through presence, empathy and understanding from professionals [1,9,13] as well as through helping the patient to think about things that renew inner peace and comfort or through measures such as relaxation, meditation, music or, for some, through religion [1].…”
Section: Spiritual Carementioning
confidence: 99%
See 1 more Smart Citation
“…As professionals, it is important to pick up on clues from patients, as informal spiritual assessment can take place anytime-for example, discussions around the search for meaning and making sense or fear or what the future holds may indicate spiritual distress [1]. Patients can then be helped to address this distress through presence, empathy and understanding from professionals [1,9,13] as well as through helping the patient to think about things that renew inner peace and comfort or through measures such as relaxation, meditation, music or, for some, through religion [1].…”
Section: Spiritual Carementioning
confidence: 99%
“…It has been suggested that general spiritual care can be provided by any member of the multidisciplinary team and includes presence, listening and compassion [1,13,25,42,43]. As professionals, it is important to pick up on clues from patients, as informal spiritual assessment can take place anytime-for example, discussions around the search for meaning and making sense or fear or what the future holds may indicate spiritual distress [1].…”
Section: Spiritual Carementioning
confidence: 99%
“…In studies conducted in Western countries [2,3,5,6,8,9,10,11,12,15], spirituality has been described in terms of "the reliance on a powerful external being, beyond the self", of "being linked with God", as involving "a search for the aim or meaning of life and for meaning in why illness has struck", and as "personal values and a sense of being".…”
Section: Introductionmentioning
confidence: 99%
“…The mean QOL score of the test group was significantly lower than that of the control group for all domains except the spiritual domain. Fryback and Reinert (1999) suggested that spirituality is an essential component to feelings of health and well-being. Many of the subjects viewed spirituality as a bridge between hopelessness and meaningfulness in life.…”
Section: International Journal Of Research Studies In Psychology 65mentioning
confidence: 99%